Neuraminidase Antibody Response to Homologous and Drifted Influenza A Viruses After Immunization with Seasonal Influenza Vaccines - Yulia Desheva; Maria Sergeeva; Polina Kudar; Andrey Rekstin; Ekaterina Romanovskaya-Romanko; Vera Krivitskaya; Kira Kudria; Ekaterina Bazhenova; Ekaterina Stepanova; Evelina Krylova; Maria Kurpiaeva; Dmitry Lioznov; et al. (Vaccines)
Background/Objectives: Humoral immunity directed against neuraminidase (NA) of the influenza virus may soften the severity of infection caused by new antigenic variants of the influenza viruses. Evaluation of NA-inhibiting (NI) antibodies in combination with antibodies to hemagglutinin (HA) may enhance research on the antibody response to influenza vaccines. Methods: The study examined 64 pairs of serum samples from patients vaccinated with seasonal inactivated trivalent influenza vaccines (IIVs) in 2018 according to the formula recommended by the World Health Organization (WHO) for the 2018–2019 flu season. Antibodies against drift influenza viruses A/Guangdong-Maonan/SWL1536/2019(H1N1)pdm09 and A/Brisbane/34/2018(H3N2) were studied before vaccination and 21 days after vaccination. To assess NI antibodies, we used an enzyme-linked lectin assay (ELLA) with pairs of reassortant viruses A/H6N1 and A/H6N2. Anti-HA antibodies were detected using a hemagglutination inhibition (HI) test. The microneutralization (MN) test was performed in the MDCK cell line using viruses A/H6N1 and A/H6N2. Results: Seasonal IIVs induce a significant immune response of NI antibodies against influenza A/H1N1pdm09 and A/H3N2 viruses. A significantly reduced ‘herd’ immunity to drift influenza A/H1N1pdm09 and A/H3N2 viruses was shown, compared with previously circulating strains. This reduction was most pronounced in strains possessing neuraminidase N2. Seasonal IIVs caused an increase in antibodies against homologous and drifted viruses; however, an increase in antibodies to drifting viruses was observed more often among older patients. The level of NI antibodies for later A/H1N1pdm09 virus in response to IIVs was statistically significantly lower among younger people. After IIV vaccination, the percentage of individuals with HI antibody levels ≥ 1:40 and NI antibody levels ≥ 1:20 was 32.8% for drift A/H1N1pdm09 virus and 17.2% for drift A/H3N2 virus. Antisera containing HI and NI antibodies exhibited neutralizing properties in vitro against viruses with unrelated HA of the H6 subtype. Conclusions: Drift A/H1N1pdm09 and A/H3N2 viruses demonstrated significantly lower reactivity to HI and NI antibodies against early influenza viruses. In response to seasonal IIVs, the level of seroprotection has increased, including against drift influenza A viruses, but protective antibody levels against A/H1N1pdm09 have risen to a greater extent. A reduced immune response to the N1 protein of the A/H1N1pdm09 drift virus was obtained in individuals under 60 years of age. Based on our findings, it is hypothesized that in the cases of a HA mismatch, vaccination against N1-containing influenza viruses may be necessary for individuals under 60, while broader population-level vaccination against N2-containing viruses may be required.